The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0207726
|View full text |Cite
|
Sign up to set email alerts
|

CSF macrophage migration inhibitory factor levels did not predict steroid treatment response after optic neuritis in patients with multiple sclerosis

Abstract: Glucocorticoid (GC) refractory relapses in patients with multiple sclerosis (MS) or clinically isolated syndrome (CIS), who are in potential need of treatment escalation, are a key challenge in routine clinical practice. The pro-inflammatory cytokine macrophage migration inhibitory factor (MIF) has been shown to be an endogenous counter-regulator of GC, and potentiates autoimmune-mediated neuroinflammation. In order to evaluate whether MIF levels are elevated in the cerebrospinal fluid (CSF) of MS patients (CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…This is consistent with other studies showing that IL6 can either not change or enhance neuronal differentiation and that these findings are dependent on its concentration ( Johansson et al, 2008 ; Islam et al, 2009 ; Zonis et al, 2013 ; Borsini et al, 2015 ). Similarly, when cells are exposed to low concentrations of IL6 (1 pg/mL) together with low concentrations of IL1β (1 pg/mL) or MIF (10 pg/mL), as found in healthy individuals ( Lindqvist et al, 2009 ; Pawlitzki et al, 2018 ), we do not observe any changes in neurogenesis. In contrast, high concentrations of IL6 (5 pg/mL) with either IL1β (10 pg/mL) or MIF (300 pg/mL), as found in depressed patients ( Piletz et al, 2009 ; Hestad et al, 2016 ; Kranaster et al, 2018 ; Tsuboi et al, 2018 ), decrease dramatically the percentage of newly generated neurons compared not only with low concentrations of the same combination of cytokines but also with the cytokines alone.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This is consistent with other studies showing that IL6 can either not change or enhance neuronal differentiation and that these findings are dependent on its concentration ( Johansson et al, 2008 ; Islam et al, 2009 ; Zonis et al, 2013 ; Borsini et al, 2015 ). Similarly, when cells are exposed to low concentrations of IL6 (1 pg/mL) together with low concentrations of IL1β (1 pg/mL) or MIF (10 pg/mL), as found in healthy individuals ( Lindqvist et al, 2009 ; Pawlitzki et al, 2018 ), we do not observe any changes in neurogenesis. In contrast, high concentrations of IL6 (5 pg/mL) with either IL1β (10 pg/mL) or MIF (300 pg/mL), as found in depressed patients ( Piletz et al, 2009 ; Hestad et al, 2016 ; Kranaster et al, 2018 ; Tsuboi et al, 2018 ), decrease dramatically the percentage of newly generated neurons compared not only with low concentrations of the same combination of cytokines but also with the cytokines alone.…”
Section: Discussionsupporting
confidence: 58%
“…—Across the experiment described below, we have used a range of concentration of cytokines based on the existing literature. Specifically, we used low and high concentrations of IL1β (1, 5 pg/mL), TNF-α (1, 10 pg/mL), MIF (10, 300 pg/mL), and IL6 (1, 5 pg/mL), as found in blood and CSF of, respectively, healthy individuals ( Lindqvist et al, 2009 ; Pawlitzki et al, 2018 ) and depressed patients ( Piletz et al, 2009 ; Hestad et al, 2016 ; Kranaster et al, 2018 ; Tsuboi et al, 2018 ). Moreover, being guided by concentrations found in blood and CSF of healthy individuals or depressed patients exposed to interventions resembling anti-inflammatory conditions ( Raison et al, 2018 ), as well as by a dose-response curve performed on our cellular model, we selected IL6 50 000 pg/mL as the most representative “anti-inflammatory” concentration of IL6.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the discrepancies is not known but may possibly depend on the relatively low number of patients and different ethnicities. It is more difficult to compare the reasons for the discrepancies between our present analysis and the study by Pawlitzki and coworkers [26], as they measured MIF levels in CSF, while we studied peripheral CD4 + T cells. Different cells, including glial cells and B cells, may contribute to the intrathecal production of MIF.…”
Section: Discussionmentioning
confidence: 57%
“…It is worth mentioning that the CSF levels of MIF have also been studied with divergent results in ON associated with MS. While one study found that CSF levels of MIF in these patients were even higher than those observed in MS relapses [25], the other observed lower levels of MIF in CSF samples of patients with MS-associated ON as compared to MS patients with stable RR-MS [26]. The reason for the discrepancies is not known but may possibly depend on the relatively low number of patients and different ethnicities.…”
Section: Discussionmentioning
confidence: 99%